Constitutionalism in the Americas - Crawford, Colin; Bonilla Maldonado, Daniel; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Constitutionalism in the Americas unites the work of leading scholars of constitutional law, comparative law and Latin American and U.S. constitutional law to provide a critical and provocative look at the state of constitutional law across the Americas today. The diverse chapters employ a variety of methodologies - empirical, historical, philosophical and textual analysis - in the effort to provide a comprehensive look at a generation of constitutional change across two continents. The authors document surprising changes, including the relative decline in the importance of U.S. constitutional jurisprudence outside U.S. borders and the growing exchange of Latin American constitutional thought within Europe and beyond. Accompanying commentary elaborates on the role of constitutional law in global changes in political, social and economic power and influence. The chapters also prompt thinking about a wide range of topics important not just in the Americas, but across the world, including the challenges and implications of using legal transplants and, conversely, the utility and potential of borrowing and adapting constitutional and other legal models to different realities. This book is useful not only for advanced students of constitutional law and theory but also for students new to the area and eager to tap into the newest thinking about constitutional law and law-making in the Americas and elsewhere.
1. Introduction / Daniel Bonilla Maldonado and Colin Crawford -- Part I The relationship between Latin American and US constitutionalism -- 2. The political economy of legal knowledge / Daniel Bonilla Maldonado -- 3. The geopolitics of constitutionalism in Latin America / Jorge L. Esquirol -- Part II Latin American constitutionalism -- 4. Constitutionalism in the Americas. A comparison between the US and Latin America / Roberto Gargarella -- 5. Back to the Future? The return of sovereignty and the principle of non-intervention in the internal affairs of the states in Latin America's "radical constitutionalism" / Javier Couso -- 6. Constitutionalism old, new and unbound: the case of Mexico / Francisca Pou Giménez -- 7. Socioeconomic rights and majoritarian courts in Latin America / David Landau -- Part III US constitutionalism in the 21st century -- 8. Constitutional drafting in Latin America. A quantitative perspective / David S. Law and Tom Ginsburg -- 9. The global diffusion of US Legal thought: changing influence, national security and legal education in crisis / Fernanda Nicola -- 10. The limits of US racial equality without a Latin American Constitutional "Right to Work" - a thought experiment / Tanya Katerí Hernández -- Index.
Obsahuje bibliografické odkazy a rejstříky
Elektronická reprodukce.
Keywords: konstitucionalismus; constitutionalism; Amerika; America; e-knihy online; e-books online